Effect of transcutaneous electrical nerve stimulation (TENS) on the Pain Intensity Phase I Stage of Labor Active In Bidan Praktik Mandiri Rahmadina Rosa 2019 - Nelly Karlinah; Berliana Irianti (Science Midwifery, 2020)
Managing labor pain takes care maternal affection which according to the WHO document describes one way to provide care that is dear mother called the Safe Motherhood. Where there are 10 steps to provide the maternal affection care delivery care in the method of pain relief without the use of drugs. TENS nonpharmacological method one can increase the comfort of the mother during labor and have an influence on effective coping to the experience of childbirth This study aims to determine "TENS effect on the first stage of labor pain intensity active phase ". This research is a quantitative research with experimental designs with post test only control group design. The study group was divided into a control group and TENS. The study was conducted in BPM Rahmadina Rosa Pekanbaru in October 2019 s / d in January 2020. Samples 20 to TENS group and 20 for the control group, so the total sample of 40 samples. Research instrument using TENS affixed to (T10-L1) and point(2-S4) on primigravida performed two times at 4 cm cervical dilatation and opening of the cervix 8 cm for 15 minutes. Using pain measurement tool Numerical Rating Scale (NRS). The results of analysis of influence between the intervention group and control the intensity TENS pain in the cervical opening 4 cm, found that most of the pain level in the medium category TENS group, while the control group level of pain mostly in the weight category. However, based on the statistical test obtained by value p> 0.05, it can be concluded there was no difference in the intervention group and the control TENS at 4 cm cervical dilatation. While the results of analysis of the effect of TENS group to the intensity of pain in the cervical opening 8 cm, shows that there is a difference between intervention and control groups, Statistical test results obtained value of p <0.05, it can be concluded that there are significant differences in the intervention group and the control TENS. TENS conclusion may affect the reduction of pain intensity in the first stage of labor is the active phase, where both are used in TENS 8 cm cervical dilatation. This means that there are differences in the perceived reduction in pain intensity respondents in the intervention group with the control.